2011
DOI: 10.3102/0002831211410305
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Collaborative Strategic Reading With Middle School Students

Abstract: The authors conducted an experimental study to examine the effects of collaborative strategic reading and metacognitive strategic learning on the reading comprehension of students in seventh-and eighth-grade English/ language arts classes in two sites (Texas, Colorado) and in three school districts. Students were randomly assigned to classes and then classes were randomly assigned to treatment or business-as-usual comparison groups. If a teacher had an uneven number of classes, we assigned extra classes to tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
196
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 160 publications
(206 citation statements)
references
References 38 publications
9
196
0
1
Order By: Relevance
“…With regards the other three studies reported in Table 2 ( Cantrell et al, 2010;Vaughn et al, 2011;Vaughn et al, 2013) it is noteworthy that all produced similar (low) effect sizes on reading comprehension outcomes. The intervention reported by Cantrell et al was intensive and delivered for 50 -60 minutes per day over the course of a year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regards the other three studies reported in Table 2 ( Cantrell et al, 2010;Vaughn et al, 2011;Vaughn et al, 2013) it is noteworthy that all produced similar (low) effect sizes on reading comprehension outcomes. The intervention reported by Cantrell et al was intensive and delivered for 50 -60 minutes per day over the course of a year.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining two studies by Vaughn et al (2011) and Vaughn et al (2013) were broadly equivalent in terms of the intensity of the interventions delivered. Both studies demonstrated gains on reading comprehension using a standardised measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, the students adopt expert roles on each of the strategies and work in small groups to comprehend a given text. Studies on CSR that included language-minority learners have demonstrated performance improvements on standardized reading exams (Boardman, Klingner, Buckley, Annamma, & Lasser, 2015;Klingner, Vaughn, Arguelles, Hughes, & Ahwee Leftwich, 2004;Klingner, Vaughn, & Schumm, 1998;Vaughn et al, 2011). As well, research on CSR outside of the language arts classroom showed promise: not only does consistent integration of CSR into science and social studies classes lead to improved reading comprehension as measured by a standardized reading test (the widely used Gates-MacGinitie Reading Test), but teachers in these content classes also provided students with substantially more reading activities (compared with traditional social and science classes) along with increased attention "to the quality of student work and providing feedback to students when using CSR" (Boardman et al, 2015(Boardman et al, , p. 1278.…”
Section: Collaborative Strategic Readingmentioning
confidence: 99%
“…Struggling readers also need instruction in thinking/comprehension strategies (Vaughn, Klinger, Swanson, Boardman, Roberts, Mohammed, & Stillman-Spisak, 2011). The comprehension strategies associated with improved results in reading achievement include: using strategies to figure out the meaning of unknown words; activating prior knowledge; self-monitoring comprehension during reading; creating graphic organizers to structure notes on texts; questioning what is being read; understanding narrative and expository text structures; and using cooperative learning to increase engagement (NICHD, 2000;Tovani, 2000).…”
Section: Specialists' Reading Practicesmentioning
confidence: 99%